2018
DOI: 10.1016/j.bone.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Body fat mass, lean body mass and associated biomarkers as determinants of bone mineral density in children 6–8 years of age – The Physical Activity and Nutrition in Children (PANIC) study

Abstract: Lean body mass (LM) has been positively associated with bone mineral density (BMD) in children and adolescents, but the relationship between body fat mass (FM) and BMD remains controversial. Several biomarkers secreted by adipose tissue, skeletal muscle, or bone may affect bone metabolism and BMD. We investigated the associations of LM, FM, and such biomarkers with BMD in children. We studied a population sample of 472 prepubertal Finnish children (227 girls, 245 boys) aged 6-8years. We assessed BMD, LM, and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 66 publications
1
30
0
1
Order By: Relevance
“…In mice, irisin produced during exercise had positive effects on cortical mineral density and geometry (93,94). In 6-8 years-old children, Soininen et al found a significant positive association between circulating irisin and BMD (95).…”
Section: Exercise and Mechanical Signals Are Anabolic To Skeletal Tissuementioning
confidence: 99%
“…In mice, irisin produced during exercise had positive effects on cortical mineral density and geometry (93,94). In 6-8 years-old children, Soininen et al found a significant positive association between circulating irisin and BMD (95).…”
Section: Exercise and Mechanical Signals Are Anabolic To Skeletal Tissuementioning
confidence: 99%
“…However, the available evidence is not completely understood, and the results of published studies have been mixed. Some studies have reported a positive association between adipose tissue and childhood bone mineral density (BMD) or bone mineral content (BMC) [17][18][19][20], whereas others have reported a negative [21][22][23] or null [24,25] association.…”
Section: Introductionmentioning
confidence: 99%
“…Leptin was also increased in offspring with less glucose tolerance. Serum leptin is correlated with body fat mass in humans 37 and mice, 38 supporting the notion of differences in body composition. This marker could also indicate a decreased appetite in MNR offspring, particularly in those with glucose intolerance.…”
Section: Discussionmentioning
confidence: 67%